Internally driven vs. externally cued movement selection: a study on the timing of brain activity - Thut, Gregor; Hauert, Claude-Alain; Viviani, Paolo; Morand, Stéphanie; Spinelli, Laurent; Blanke, Olaf; Landis, Theodor; Michel, Christoph (Brain research. Cognitive brain research, 2000)
Brain imaging studies in man and single cell recordings in monkey have suggested that medial supplementary motor areas (SMA) and lateral pre-motor areas (PMA) are functionally dissociated concerning their involvement in internally driven and externally cued movements. This dichotomy, however, seems to be relative rather than absolute. Here, we searched for further evidence of relative differences and aimed to determine by what aspect of brain activity (duration, strength, or both) these might be accounted for. Event-related potentials (ERPs) were recorded while healthy, right-handed subjects selected one of three possible right hand digit movements based either on `internal' choice or `external' cues. The results obtained from ERP mapping suggest that movement selection evokes the same electrical brain activity patterns in terms of surface potential configurations in the same order and at the same strength independent of the selection mode. These identical configurations, however, differed in their duration. Combined with the results of a distributed source localization procedure, our data are suggestive of longer lasting activity in SMA during the `internal' and longer lasting activity in PMA during the `external' condition. Our results confirm previous findings in showing that SMA and PMA are distinctively involved in the two tasks and that this functional dichotomy is relative rather than absolute but indicate that such a dissociation can result from differences in duration rather than pure strength of activation.